Capsicum Apps: Creating Innovation Space of Chili Supply Chain through the Triple Helix Model in Central Java Indonesia - Suko Irawan; Sri Astuti; Nanda Mei Istiqomah; Ernoiz Antriyandarti (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2022)
The paper aims to clarify the relationship between the Triple Helix concept and the logistic cultivation Distribution of chilli in Central Java. It proposes modelling the education and distribution transformation process through Capsicumm apps in industrial 4.0. This study used a qualitative approach to seeking the truth by discovering the essence. Conducted participant observation approach, the researcher, is directly involved as active agents and sources of information, participates for comprehensively discuss the role of Triple Helix Model which has been developed by the Value Chain Center (VCC) in the development of chilli supply chain management which involves the small farmers to fulfil the global market demands. Chilli is one of the essential commodities in Indonesia, and every region has different conditions of the vegetable trading system. The difference is caused by the additional amount of marketing agencies and supply chain management roles. Central Java is the province that has the longest chain of red chilli distribution. Chilli production that fluctuates annually causes the unstable selling price of chilli commodities, affecting chilli farmers' welfare and inflation. The paper contributes in providing empirical insights about the role of the Triple Helix Concept and how to change information In the industrial 4.0 era to optimize cultivation and logistic Distribution Chilli through Capsicum Apps.